Homelessness of Children as a Social Phenomenon in 1941-1945: Manifestations and Attempts to Overcome in Middle Volga - R. A. Mukhamedov; A. G. Pashkin (Научный диалог)
The article is devoted to the analysis of the main directions and specifics of the activities of state bodies and public organizations of the Middle Volga region in the fight against children homelessness in 1941-1945. At the present stage of Russia’s development, the government and society are paying considerable attention to eliminating crime and preventing deviant behavior among minors, which in turn strengthens the urgency of the problem. The authors introduce into the scientific circulation previously unavailable documents of the State Archive of the Ulyanovsk Region, the State Archive of Recent History of the Ulyanovsk Region, the Samara Regional State Archive of Socio-Political History. The reasons for the development of homelessness, its scope are analyzed in detail in the article, and also the key areas of activity of the internal affairs bodies are considered. It is proved that in the initial period of the Great Patriotic War in the territory of the Middle Volga region a number of factors were recorded that contributed to the criminalization of minors: significant population migration, unstable work of railway and water transport, the termination of educational institutions, an increase in the number of street and street children. It is shown that the answer to the challenge was the development of a method for combating juvenile crime, based on the close interaction of law enforcement, educational bodies and public organizations. It is alleged that the use of new methods has partially reduced the impact of negative trends and, consequently, improved the criminal situation among minors.